The Existence, Function, and Legal Position of the Land Bank According to the Provisions of the Laws and Regulations - Alwinda, Erin; Wafirah, Athifatul; Roring, Pingkan Vanesa; Onthoni, Lefira Gerti (Universitas Ekasakti, 2023)
This article discusses the existence, function and legal position of the Land Bank after the Constitutional Court Decision and also examines the existence of Customary Land after the existence of the Land Bank Institution in Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja. Where after the birth of Undang-Undang Cipta Kerja, there were several test applications submitted to the Constitutional Court and ruling on this formal test case, the Government was ordered to make improvements within a period of 2 years if within that period no improvements were made, then UU Cipta Kerja would become permanently unconstitutional and it was also not allowed to issue new implementing regulations relating to UU Cipta Kerja. UU Cipta Kerja is also reviewed in relation to licenses to use customary land of indigenous peoples, where indigenous peoples feel they are losing their rights because there are no legal remedies against business actors who use customary land as land for business without having to get approval from indigenous peoples.